Casa Melnikov. Racionalismo en la Unión Soviética - Pascal de Marzo, Ramiro Percy (2015)
Konstantine Melnikov’s work is a representative apartment in the twentieth century, where the combination between the ideas of modern space combined with the limited techniques that adapt to a crisis and scarcity as the Soviet Union was at the mid-twentieth century. The unique geometry and possibilities of craft construction but designed from mass production, and the development of vertical space make this work one of the most important buildings of modern european architecture. The analysis addresses these variables, and seeks to raise its importance as a subject of study.